Laxative Activity Test of Gynura procumbens (Lour.) Merr. Leave on White Male Mice Induced by Loperamide - Uthia, Rahimatul; Prima Yolanda, Devina; Eriadi, Aried; Dinni Aulia Bakhtra, Dwi (Metamorfosa: Journal of Biological Sciences, 2019)
Constipation is a symptom of a problematic, non-smooth and irregular defecation process. While laxative is a substance that stimulates intestinal peristalsis as a reflex of direct stimulation of the intestinal wall that can cause or facilitate defecation. This study aimed to determine the ethanol extract of the leaves of Gynura procumbens (L.) Merr. effect as a laxative in white male mice induced by loperamide. The methods used for laxative testing are defecation patterns and intestinal transit methods. The parameters observed included frequency of defecation, stool consistency, stool weight every 30 minutes for 4 hours, and the length of the activated carbon in the mice's intestine. The extract was administered orally at a dose of 75 mg/kg BW, 150 mg/kg BW and 300 mg/kg BW, as a comparison used negative control (Na CMC). From the results of the study, it was found that the administration of ethanol extracts of Gynura procumbens (Lour.) Merr. leaves at the dose of 150 mg/kg BW gave laxative activity to white male mice (P <0.05).